2018
DOI: 10.26803/ijlter.17.6.7
|View full text |Cite
|
Sign up to set email alerts
|

Debriefing Program for Prospective Elementary School Teachers in Developing Learning Aids

Abstract: Abstract. This research was conducted to develop a debriefing program for prospective elementary school teachers in order to develop contextbased learning aids and its assessment. Reeves Design Based Research (DBR) model was employed as a research design, and its data were processed descriptively. A field needs analysis was conducted to students who have taught at school through an analysis of common learning aids and questionnaires. Early debriefing programs were developed based on field needs analysis. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…The research conducted by Mappeasse [16], Nelasari [7], Wahyudi [17], and Hamdu [18] concluded that there was a contribution between student's motivation variables to student learning outcomes. From the previous research can be concluded that the students who have high learning motivation will get good learning outcomes.…”
Section: The Contribution Of Learning Motivation Towards Results Of Cmentioning
confidence: 99%
“…The research conducted by Mappeasse [16], Nelasari [7], Wahyudi [17], and Hamdu [18] concluded that there was a contribution between student's motivation variables to student learning outcomes. From the previous research can be concluded that the students who have high learning motivation will get good learning outcomes.…”
Section: The Contribution Of Learning Motivation Towards Results Of Cmentioning
confidence: 99%
“…3) Setiap isian siswa dalam LKS alangkah baiknya diberi semacam refleksi atau kesimpulan. 4) penulisan kesimpulan tidak harus dituliskan "kesimpulan", namun bermakna pernyataan tersirat (Hamdu dan Sopandi, 2018).…”
Section: Pendahuluanunclassified
“…Even this ATK model encourages an increase in teacher academic performance through the mechanism of "Absorbing, Doing, Interacting, and Reflecting" (ADIR), as an educational process that opens opportunities for the growth of learning independence, so that the increase in professionality of chemistry teachers can run continuously. Because of that, a program to improve the professional competence of teachers is vital to be conducted (Hamdu, Sopandi, & Nahadi, 2018). Teachers' and learners' empowerment also can be improved through connecting the Use of Educative Curriculum Materials to Students' Engagement in Science Argumentation (Arias, Smith, Davis, Marino, Palincsar, 2017) or use of multimedia (Loper, Katherine, McNeill, González-Howard, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%